From secularism to Jihad: Sayyid Qutb and the foundations of radical Islamism - Musallam, Adnan (Praeger, 2005)
Prologue -- Intellectual, political and socio-economic transformations in egypt, 1919-1952 -- Qutb's childhood and the emergence of a poet and a critic, 1906 - 1938 -- Emergence of the student of the Qurʾan and early changes, 1939-1947 -- The alienation of Sayyid Qutb, 1939-1947 -- In search of social justice : the emergence of an independent Islamic ideologue, 1947-1948 -- Qutb's experiences and impressions in America, 1948-1950 and his return, 1950-1952 -- Emergence of a radical Islamist, 1952-1964 -- Martyrdom, posthumous impact and global Jihad -- Epilogue